Making of Navi Mumbai - Shaw Annapurna (New Delhi Orient Longman, 2004)
This book uses the case of the Navi Mumbai urban project to bring out many of the problems inherent in the urbanisation process and in the nature of urban policy-making in post-colonial India. It illustrates how even a new city, built from scratch, is ri
Keywords: India; New Bombay; Urbanization